Muslim Consumers' Purchasing Decisions on Halal Food Products Using Online Delivery Services During the Covid-19 Pandemic: Lessons from Bogor City, Indonesia - Shatrie, Firly Mariska; Wiliasih, Ranti; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal (Dirham: Journal of Sharia Finance and Economics, 2025)
Purpose: This study aims to explore the factors influencing halal food consumption and purchasing decisions during the COVID-19 pandemic in Bogor City, Indonesia, focusing on the impact of religious beliefs, health consciousness, and safety concerns. Methods: A quantitative approach was employed, utilizing a survey conducted with 200 consumers in Bogor City. Data were collected using a structured questionnaire and analyzed using SPSS for descriptive statistics and regression analysis. Results: The results show that religious beliefs significantly affect halal food purchasing decisions, with health consciousness and safety concerns also playing a vital role. The pandemic heightened the importance of food safety and health among consumers, influencing their purchasing behavior. Conclusion: The findings suggest that halal food consumption is strongly influenced by religious factors, while health-related concerns have gained prominence during the pandemic. This highlights the growing importance of safety and quality in consumers' decision-making processes. Limitation: The study is limited to Bogor City, which may not fully represent other regions in Indonesia. Additionally, the sample size of 200 respondents may not capture the diversity of the broader population. Contribution: This study contributes to the understanding of consumer behavior in the context of halal food and provides valuable insights for businesses in the food industry to adapt their strategies in the post-pandemic era, particularly in Muslim-majority countries.